Pengaruh Marketing Media Sosial Instagram Terhadap Citra Merek - Ade Rifki Hamdani Lubis; Rahmat Hidayat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The proliferation of coffee shops creates intense competition. Coffee shop managers are competing to provide excellent service to all consumers, such as coffee quality, completeness of food / beverage companions, visitor comfort and safety, coffee shop design, to try to increase the electability of the brand owned or what is referred to as brand image. The purpose of this study was to determine whether there was an influence of Instagram social media marketing on brand image at the Dukku Riang Coffee Shop Medan. The sample for this research is 76 people from the number of followers of the account @dukku.riang. Sampling using simple random sampling, namely the determination of samples that provide equal opportunity to each member of the population to be sampled. Sampling using the Slovin formula. Data analysis used the Simple Regression test, while data processing used SPSS. The results of the study show that Instagram social media marketing affects brand image at Dukku Riang Coffee Shop Medan.